Life and the Spiritual Practice of Senior Citizens in Kalpabaas of Devghat, Chitwan - Subedi, Laxman (Journal of Bhuwanishankar, 2024)
As the years increase, senior citizens' needs and desires drive from normal to spiritual lifestyles. The Kalpabaas system is one of the systems found for spiritual practice, basically for senior citizens. The term Kalpabaas is a new term to the researcher, which denotes the meaning of the period of Brahma, the god of creation. It is believed that anyone who lives in a Kalpabaas following the prescribed rules and regulations can obtain the Punya of a Kalpa, which means a day of Brahma. Exploring the system and the life of Kalpabaas and the spiritual practice of senior citizens are the objectives of this research. Thirteen participants, who have been living in Devghat, being Kalpabaasi, for more than a decade, were purposively selected from Devghat Chitwan, and they were in-depth interviewed until the saturation of the data. Grounded theory is adopted as the theoretical standpoint. Perception of Kalpabaas, the requirement to be a Kalpabaasi, spiritual knowledge of the devotees, everyday life activities, Satasanga, participating in the spiritual ceremonies, and so on activities were found performed in Kalpabaas. A simple lifestyle, negligence in modernity, less desire, a higher level of understanding of the religious and spiritual lesson, a focus on the divine power, poor health, and a weak body but brightness in the face were found features of Kalpabaasi.